Prediction of fatigue crack initiation under biaxial loading - J.V. Sahadi; D. Nowell; R.J.H. Paynter (Fracture and Structural Integrity)
This investigation revisits biaxial fatigue experiments carried out with the nickel-based superalloy termed Waspaloy. Recently, yield criteria extended to multiaxial fatigue and stress based approaches were analysed and their performance to correlate the biaxial test data was evaluated. It was concluded that despite their reliable results, the parameters did not properly represent the physical behaviour of the material. In this context, an extension of this study was executed considering the strain based critical plane approaches proposed by Fatemi-Socie (FS) and Smith- Watson-Topper (SWT). The first parameter presented overly conservative predictions with large scatter of results. In contrast, more accurate predictions were obtained with the SWT parameter.